PELATIHAN PERHITUNGAN HARGA POKOK PRODUKSI UMKM DI DUSUN KRAJAN 1B - Siti Nabila; Nurma Risa; Rusham Rusham (Universitas Islam 45 Bekasi, 2022)
The confusion of the SMEs (Micro, Small and Medium Enterprises) in Kutagandok Krajan 1B village is very clear. When asked Perilla how to determine the selling price of the products they will produce. The confusion of MSME actors stems from not knowing exactly how much the production costs of the products they have produced. This service activity aims to train MSME actors in Kutagandok Krajan 1B village in terms of determining the cost of production of the products they have produced, so that MSME actors can determine the selling price that will affect the profits or losses of MSME actors in the Kutagandok Krajan IB village. There are three methods used in this service activity, namely the method of lecture method, training methods, and discussion methods. The results of this service activity will provide insight and understanding to MSME actors in Kutagandok Krajan IB village about calculating production costs. This insight and understanding is reflected in the discussion method. In the discussion method, there will be many MSME actors who will ask questions about material that has not been understood, thus showing the enthusiasm of MSME actors for training in calculating production costs which is quite high.